Analisis Hukum Islam dan Pasal 4 UU Pengelolaan Zakat No. 23 Tahun 2011 terhadap Pelaksanaan Zakat Pertanian di Desa Ciranggon Kabupaten Karawang - Amalia solihat; Siska Lis Sulistiani; Intan Nurrachmi (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. Agricultural zakat is one of the zakat maal which has its own rules regarding nishab and the type of agriculture according to Islamic law and Law Number 23 of 2011 concerning Zakat Management, especially Article 4. In this regard, farmers in Ciranggon Village, Karawang Regency carry out agricultural zakat without knowledge of the rules. nishab and zakat management mechanisms that are not in accordance with applicable legislation. Based on these problems, the focus of this study aims to determine the analysis of Islamic law on the implementation of agricultural zakat in Ciranggon Village, Karawang Regency, and to determine the analysis of Article 4 of the Zakat Management Act No. 23 of 2011 on the implementation of agricultural zakat in Ciranggon Village, Karawang Regency. The research method used is descriptive analysis with a normative juridical approach, namely analyzing the level of conformity of the implementation of agricultural zakat in Ciranggon Village with Islamic Law and Article 4 zakat management of Law no. 23 of 2011. The results show that the analysis of Islamic legal views on the practice of agricultural zakat in Ciranggon Village, Karawang Regency is not fully in accordance with the provisions of Islamic Law, especially related to nishab and the implementation of agricultural zakat practices in Ciranggon Village, Karawang Regency also not fully in accordance with the provisions of Article 4 of the Law. zakat management no. 23 of 2011 especially in the care of zakat that is not through an official amilin agency or institution. Abstrak. Zakat pertanian merupakan salah satu zakat maal yang memiliki aturan tersendiri terkait nishab dan jenis pertaniannya menurut Hukum Islam maupun UU Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat khususnya Pasal 4. Terkait hal tersebut, para petani di Desa Ciranggon Kabupaten Karawang melaksanakan zakat pertaniannya tanpa pengetahuan mengenai aturan nishab dan mekanisme pengelolaaan zakatnya yang tidak sesuai perudang-undangan yang berlaku. Berdasarkan permasalahan tersebut, maka fokus penelitian ini memiliki tujuan agar bisa diketahui Analisis Hukum Islam Pada pelaksanaan zakat pertanian di Desa Ciranggon Kabupaten Karawang, dan untuk mengetahui analisis Pasal 4 UU pengelolaan zakat No. 23 Tahun 2011 terhadap pelaksanaan zakat pertanian di Desa Ciranggon Kabupaten Karawang. Penelitian ini memiliki metode yakni analisis deskriptif, sedangkan penelitian memiliki pendekatan yakni analisis deskriptif dengan pendekatan yuridis normatif yaitu menganalisis tingkat kesesuaian pelaksanaan zakat pertanian di Desa Ciranggon dengan Hukum Islam dan pasal 4 pengelolaan zakat UU No. 23 tahun 2011. Dimana penelitian ini memiliki hasil jika pandangan hukum Islam terhadap praktik zakat pertanian di Desa Ciranggon Kabupaten Karawang belum sepenuhnya selaras pada ketentuan Hukum Islam khususnya terkait nishab dan pelaksanaan praktik zakat pertanian di Desa Ciranggon Kabupaten Karawang juga belum sepenuhnya sesuai dengan ketentuan Pasal 4 UU pengelolaan zakat No. 23 Tahun 2011 khususnya dalam penitipan zakat yang tidak dengan melewati Badan atau Lembaga amilin resmi.